ANALYSIS OF THE ESSENTIAL OIL EXTRACTED FROM THE LEAVES OF JUSTICIA PECTORALIS JACQ. (ACANTHACEAE) WITH POTENTIAL FOR PHYTOTHERAPEUTIC PRESCRIPTION (CIPEEX, 2025)
Introduction: Essential oils are volatile, strongly aromatic liquids extracted from plants. The Acanthaceae family has medicinal value due to its high capacity for essential oil extraction. The importance of these oils is primarily related to their economic value, along with their already proven therapeutic properties. Objective: To analyze the phytotherapeutic potential of the essential oil extracted from the leaves of Justicia pectoralis Jacq. Methodology: Essential oils were extracted from the leaves of Justicia pectoralis using hydrodistillation with a modified Clevenger-type apparatus. The chemical composition was analyzed by gas chromatography coupled with mass spectrometry (GC/MS). Results: Chromatographic analysis identified 49 components of the plant, with 9 main constituents. The most prevalent were monoterpenes (12.5%) and sesquiterpenes (82.5%). The compound (E)-caryophyllene, present in significant amounts, demonstrated promising pharmacological activities, such as anti-inflammatory and antimicrobial effects. Conclusion: The analysis of essential oils of J. pectoralis revealed a characteristic terpenoid profile, with a predominance of sesquiterpenes. Further genotoxic and cytotoxic evaluations are still necessary. Therefore, the oil can be explored for therapeutic and commercial use.
Keywords: Essential oil; Justicia pectoralis; Phytotherapy